Estudo da produção de calor metabólico em caprinos manejados no semi-árido nordestino - Domingos, Hérica Girlane Tertulino (Universidade Federal Rural do Semi-Árido, 2012)
This study aimed to assess the daily variation of metabolic heat production in goats based on oxygen consumption and carbon dioxide production in association with meteorological variables and physiological responses. 10 SPRD goats were used, four with predominantly white fur and six with predominantly black. The observations were made with the protected and exposed animals to direct sunlight, in a period of 12 days during the months of August and September, 2010 in Mossoró-RN. The metabolic heat production (M, Wm-2), the latent heat flow from the respiratory system (ER, Wm-2) and from the cutaneous surface (ESC Wm-2) were determined simultaneously through a face mask and a ventilated capsule, respectively. We also measured the rectal temperature, surface temperature and respiratory rate and measured the environmental variables, air temperature, black globe temperature, wind speed, air humidity, partial vapor pressure and solar radiation. Analysis of variance was based on least-squares method and comparison of means was done by Tukey's test at 5% level of significance. The results showed that the semi-arid goats maintained stable to metabolic heat production during the day, however, when exposed to direct sunlight, significantly increased the latent heat loss in the cutaneous surface and reduced metabolic heat production approximately 24% in an attempt to maintain constant internal temperature
Metabolic heat production in goats managed in semiarid region
Keywords: Indirect calorimetry; latent heat loss; shade; solar radiation; Thermal equilibrium; Caprinos; Produção de calor metabólico; Perda de calor latente; Calorimetria indireta; Semiárido; CIENCIAS AGRARIAS::MEDICINA VETERINARIA